African-centered schooling in theory and practice - Pollard, Diane; Ajirotutu, Cheryl; Epps, Edgar G., 1929- (Bergin & Garvey, 2000)
Annotation Given the increasing interest in African-centered education as a viable alternative educational strategy, the present study, growing out of the African American Immersion Schools Evaluation Project, provides an important demonstration of the movement from theoretical discussions of the potential benefits of African-centered education to its practice and measurable outcomes in urban public schools. The similarities between Milwaukee and other urban schools districts indicate that the findings from this study should have wide applicability.